PENGGUNAAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA PADA MATERI ASMAUL HUSNA KELAS IV SD NEGERI 1 NGASEM - Aprilia, Eka Fitri; Mulyono, Mulyono; Hady, M Samsul (Muta'allim: Jurnal Pendidikan Agama Islam, 2023)
This research is based on the issue of how to improve students' engagement in the learning process by using audiovisual media on the subject of Asmaul Husna in the fourth-grade class at SD Negeri 1 Ngasem, Ngajum District. The objective of this research is to determine the improvement of students' engagement in the learning process by using audiovisual media on the subject of Asmaul Husna in the fourth-grade students of SD Negeri 1 Ngasem. This research employs a classroom action research with two cycles. Each cycle consists of four stages: planning, implementation, observation, and reflection. The target of this research is the fourth-grade students in the academic year 2022-2023. The data obtained include observation sheets, interviews, and documentation. The analysis results indicate that students' learning engagement has improved from Cycle I to Cycle II. In the pre-cycle, students' learning engagement reached 62.5% in the moderate category. In Cycle I, the percentage of students' learning engagement was only 25% in the high category. The teacher made improvements in Cycle II, resulting in an increase to 75% in the high category. The conclusion of this research is that the use of audiovisual media can enhance the learning engagement of fourth-grade students at SD Negeri 1 Ngasem, and this audiovisual media can be used as an alternative for Islamic Religious Education (PAI) learning. Abstrak proses pembelajaran dengan menggunakan media audio visual pada materi asmaul husna kelas IV SD Negeri 1 Ngasem Kec.Ngajum. Sedangkan tujuan dari penelitian ini adalah untuk mengetahui peningkatan keaktifan siswa dalam proses pembelajaran dengan menggunakan media audio visual pada materi asmaul husna pada siswa kelas IV SD Negeri 1 Ngasem. Penelitian ini menggunakan penelitian tindakan kelas dengan dua siklus. Setiap siklus terdiri dari empat tahap, yakni perencanaan, pelaksanaan, observasi, refleksi. Sasaran penelitian ini adalah siswa kelas IV Tahun pelajaran 2022-2023. Data yang diperoleh berupa lembar observasi, wawancara, dan dokumentasi. Dari hasil analisa didapatkan bahwa keaktifan belajar siswa mengalami peningkatan dari siklus I sampai siklus II yaitu, pada pra siklus keaktifan belajar siswa mencapai 62,5% pada kategori sedang, pada siklus I persentase keaktifan belajar siswa hanya sebesar 25% pada kategori tinggi, kemudian guru melakukan perbaikan pada siklus II sehingga meningkat menjadi 75% dengan kategori tinggi. Simpulan dari penelitian ini penggunaan media audio visual dapat meningkatkan keaktifan belajar siswa kelas IV SD Negeri 1 Ngasem serta media audio visual ini dapat digunakan sebagai salah satu alternatif pembelajaran PAI.